The recognition of misfolded glycoproteins in the endoplasmic reticulum - Thomas, David Y. (Henry Stewart Talks, 2012)
The endoplasmic reticulum, Protein folding, Molecular chaperones, N-glycosylation, Lectin-type chaperones calnexin and calreticulin, Link between protein folding and glycosylation, ER quality control